2023
DOI: 10.3389/fphys.2022.1055234
|View full text |Cite
|
Sign up to set email alerts
|

Placental treatment with insulin-like growth factor 1 via nanoparticle differentially impacts vascular remodeling factors in guinea pig sub-placenta/decidua

Abstract: Clinically, fetal growth restriction (FGR) is only detectable in later gestation, despite pathophysiological establishment likely earlier in pregnancy. Additionally, there are no effective in utero treatment options for FGR. We have developed a nanoparticle to deliver human insulin-like 1 growth factor (hIGF-1) in a trophoblast-specific manner which results in increased expression of hIGF-1. IGF-1 signaling in the placenta regulates multiple developmental processes including trophoblast invasion and maternal v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…It is widely accepted that male fetuses are more susceptible to worse outcomes when affected by in utero disorders and perform more poorly in the NICU than female fetuses and neonates 38, 39 . We previously identified sexually dimorphic responses with both our MNR model and our IGF1 treatment in fetuses, recapitulating the human scenario 23, 40, 41 . While we had no directly treated female placentas, indirectly treated female placentas showed more significant IGF signaling changes in receptor, binding partner, and Igf2 mRNA levels than males, highlighting dimorphic responses based on sex.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It is widely accepted that male fetuses are more susceptible to worse outcomes when affected by in utero disorders and perform more poorly in the NICU than female fetuses and neonates 38, 39 . We previously identified sexually dimorphic responses with both our MNR model and our IGF1 treatment in fetuses, recapitulating the human scenario 23, 40, 41 . While we had no directly treated female placentas, indirectly treated female placentas showed more significant IGF signaling changes in receptor, binding partner, and Igf2 mRNA levels than males, highlighting dimorphic responses based on sex.…”
Section: Discussionmentioning
confidence: 73%
“…Thus far in our nanoparticle therapy studies we have successfully delivered plasmids ex vivo and in vitro to human syncytiotrophoblast and in vivo to mouse, guinea pig, and non-human primate models and shown physiochemical properties, cellular safety, and efficiency in both mother and fetus 23, 24, 28 . We have also shown that administration of this gene therapy to the placenta in a normal pregnancy environment results in homeostatic responses within the placenta maintaining normal fetal growth and no placentomegaly 22, 28 . Previous studies using the guinea pig model of FGR from our lab have focused on short term effects of our nanoparticle-mediated IGF1 at mid-pregnancy and showed positive improvements to the placenta that could improve fetal growth, so this study employed multiple IGF1 treatments across later gestation to assess longer term impact on placental function, fetal weight and maternal environment.…”
Section: Introductionmentioning
confidence: 88%
“…However, we have also shown that administration of this nanoparticle gene therapy to the placenta in a normal pregnancy environment results in down-regulation of decidual and placental mTOR signaling and growth factor gene expression in order to maintain placental homeostasis. 23…”
Section: Methodsmentioning
confidence: 99%
“…However, we have also shown that administration of this nanoparticle gene therapy to the placenta in a normal pregnancy environment results in down-regulation of decidual and placental mTOR signaling and growth factor gene expression in order to maintain placental homeostasis. 23 Animal care and transuterine, intraplacental nanoparticle administration Animal care and usage was approved by the Institutional Animal Care and Use Committees at Cincinnati Children's Hospital and Medical Center (Protocol number 2017-0065) and University of Florida (Protocol number 202011236). Detailed information on animal care, maternal nutrient restriction (MNR) implementation, and ultrasound-guided transuterine, intra-placental nanoparticle administration can be found in Wilson et al, 2022.…”
Section: Polymer Synthesis and Nanoparticle Formationmentioning
confidence: 99%
“…Nanoparticles offer promise as a clinically relevant vehicle for delivery of therapeutics to the placenta. We have previously demonstrated that a non-viral poly [2-hydroxypropyl] methacrylamide (HPMA) – poly(2-(N,N-dimethylamino) ethyl methacrylate (DMAEMA) co-polymer complexed with plasmid containing human insulin-like growth factor 1 ( hIGF1 ) under the control of a placenta-specific promoter can be successfully delivered in vivo to pregnant mice 6 and guinea pigs 7, 8 , ex vivo to human placental explants 9, 10 and in vitro to human trophoblast cultures 6, 9, 10 . IGF signaling is essential to placental development and function by promoting trophoblast proliferation, syncytialization, invasion, migration and uptake of amino acids and glucose 11 .…”
Section: Introductionmentioning
confidence: 99%